The impact of antenna orientation on wireless sensor network performance - Wadhwa, M.; Min Song; Rali, V.; Shetty, S. (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
In this paper, we investigate the impact of antenna orientation on the performance of wireless sensor networks. In the experiments conducted using Crossbow MicaZ motes we realized that the antenna orientation has a significant impact on the received signal strength (RSSI). It thus becomes important to incorporate the effects on RSSI due to variations in antenna orientations while performing simulations and analyzing the performance of wireless sensor networks. We have successfully validated the experimental results with an analytical model. The significant deviations have been explained based on other factors that affect the performance of wireless sensor networks, viz. mulitpath, interference etc. However, it must be noticed that we do not generalize the results obtained, as it depends upon the type of antenna used, and in our case, it is a quarter wavelength tilt and swivel antenna that is usually used for MicaZ sensor motes. In order to determine the routing path from one node to the other, we propose Distance and Orientation based Protocol for Energy conservation, or in short DOPE. Using this protocol, the data is routed based on the least energy consuming path. Matlab simulation of sensor network yields that if the data is routed from one node to the other based on antenna orientation consideration, a lot of energy (on an average 30 percent) can be saved as compared to the networks where antenna orientation is not taken into consideration.